Choosing justice : an experimental approach to ethical theory - Frohlich, Norman; Oppenheimer, Joe A. (Berkeley, CA : University of California Press, 1992)
This book presents an entirely new answer to the question: "What is fair?" In their radical approach to ethics, Frohlich and Oppenheimer argue that much of the empirical methodology of the natural sciences should be applied to the ethical questions of fairness and justice.
Frontmatter -- Contents -- Figures and Tables -- Acknowledgments -- Introduction: Understanding Distributive Justice -- CHAPTER ONE. Empirical Considerations Concerning Impartial Reasoning -- CHAPTER TWO. Research Problems -- CHAPTER THREE. Research Design -- CHAPTER FOUR. Basic Results Impartial Choices -- CHAPTER FIVE. Explaining Group Choices of Principles -- CHAPTER SIX. Group Choices of a Floor Constraint -- CHAPTER SEVEN. The Role of Experimental Factors in Individual Choices -- CHAPTER EIGHT. Stability of Preferences and Satisfaction in a Working Environment -- CHAPTER NINE. Redistribution and Productivity -- CHAPTER TEN. Implications for Ethical Inquiry and Social Policy -- APPENDIX A. Subject Handbook -- APPENDIX B. Choices of Principles by Experimental Type -- APPENDIX C. Analyzing the Role of Background and Attitudinal Variables -- APPENDIX D. Analyzing the Effect of Location on the Level of Floor Constraint -- APPENDIX E. Analyzing Changes in Support for Principles by Rankings -- APPENDIX F. Production Documents -- APPENDIX G. Setting the Imposed Principle -- References -- Index
Includes bibliographical references (pages 247-251) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Distributive justice; Income distribution; Social choice; Justice distributive; Revenu -- Répartition.; Choix collectif; BUSINESS & ECONOMICS -- Business Ethics; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; PHILOSOPHY / Ethics & Moral Philosophy; Distributive justice; Income distribution; Social choice